2011
DOI: 10.1080/09712119.2011.607920
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pituitary specific transcription factor-1 gene polymorphism in several indigenous Chinese cattle and crossbred cattle

Abstract: Since mutations on POU1F1 gene possibly resulted in deficiency of growth hormone (GH), prolactin (PRL), thyroid-stimulating hormone (TSH) and pituitary specific transcription factor-1 (POU1F1), this study revealed the polymorphism of cattle POU1F1-HinfI locus and analyzed the distribution of alleles on eight cattle breeds including five indigenous Chinese cattle and three crossbred cattle breeds. The PCR-RFLP analysis showed that allele B was the dominant allele. The frequencies of allele B varied from 0.535 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Zhou et al (2016) found an association between the POU1F1/AluI locus and the LMY, while other authors have reported associations between different parts of the POU1F1 gene and the LMY (Özmen et al, 2014;Lan et al, 2013;Mura et al, 2012) and milk production traits in cattle (Khaizaran and Al-Razem, 2014). However, in the study conducted by Huang et al (2008), a significant effect of the POU1F1 gene on the LMY was observed only for exon 3, whereas no effect was observed for intron 5 nor exon 6 (Trakovicka et al, 2014;Yan et al, 2011). In our study, the TC genotype of POU1F1 was associated with a longer lactation length compared with the CC and TT genotypes.…”
Section: Discussioncontrasting
confidence: 59%
“…Zhou et al (2016) found an association between the POU1F1/AluI locus and the LMY, while other authors have reported associations between different parts of the POU1F1 gene and the LMY (Özmen et al, 2014;Lan et al, 2013;Mura et al, 2012) and milk production traits in cattle (Khaizaran and Al-Razem, 2014). However, in the study conducted by Huang et al (2008), a significant effect of the POU1F1 gene on the LMY was observed only for exon 3, whereas no effect was observed for intron 5 nor exon 6 (Trakovicka et al, 2014;Yan et al, 2011). In our study, the TC genotype of POU1F1 was associated with a longer lactation length compared with the CC and TT genotypes.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies evaluating Pit-1-HinfI polymorphism in Holsteins bred in Iran (9,12), Poland (10), Italy (36) and China (43) found that the frequency of the Pit-1-B allele was much higher than that of the A allele frequency at 0.830 and 0.70, respectively. In the present study of Holstein cattle, BB was genotype found at the highest frequency with a value between 0.569 and 0.742 and the AA genotype was present at the lowest frequency, between 0.007 and 0.054.…”
Section: Discussionmentioning
confidence: 90%
“…Further, it was significantly linked with milk production in goat and sheep (Lan et al, 2009 c ;Ozmen et al, 2014); with litter size in Awassi sheep and Shaanbei W hite Cashmere goat (Al-Khuzai and Al-Anbari 2018; Zhu et al, 2019). The POU1F1 gene mutations also exhibited a positive association with milk protein in cattle (Yan et al, 2011); growth and carcass traits of swine (Getmantseva et al, 2017).…”
Section: Association Of Exon-6 Pou1f1 Gene Polymorphism With Body Wei...mentioning
confidence: 99%